Intermediate-term outcomes of pars plana tube insertion of Aurolab aqueous drainage implant for refractory glaucoma. Issue 9 (3rd December 2019) - Babu, Naresh; Baliga, Girish; Wijesinghe, Hiruni Kaushalya; Puthuran, George Varghese
Abstract : Purpose: To report the safety and efficacy of parsplana tube insertion of Aurolab aqueous drainage implant(AADI) in patients with refractory glaucoma. Methods: Charts of patients with refractory glaucoma who underwent AADI via the parsplana route between June 2014 and June 2018with a minimum follow-up of 6 months were retrospectively reviewed. Success was defined as complete when the intraocular pressure (IOP) was ≥5 and18 mmHg or IOP reduction was > 30%from baseline without antiglaucoma medication (AGM) andas qualified if requiring additional AGMs. Results: The study included 63 eyes of 63 patients with a mean age of 36.1±20.6 years and a mean follow-up of 19.7±15.7 months. Glaucoma postvitreoretinal surgery was the the most common aetiology (22 eyes, 35%). The mean IOP reduced from 36.6±10.7 mmHg to15.7±8.2 (57.1%), 15.02±7.3 (60%) and 17.2±8.5 mmHg (53%)at 6 months and 1 and 2 years, respectively. Kaplan-Meier estimates showed that the cumulative probabilities of failure were 8% (95% CI4.3% to 22.4%) at 6 months, 23% (95%CI12.8% to 38.6%) at 1 year, 30% (95%CI17.4% to 45.9%) at 18 months and 47% (95% CI13.4% to 64.9%) at the 2 years time points.Vitreous blocking tube tip was noted up to 8% of eyes on follow-up. Conclusion: Pars plana AADI insertion is a useful procedure for the control of IOP in patients with refractory glaucoma.